Cheilolejeunea morganii Bever. & Glenny (Lejeuneaceae, Marchantiopsida), a newly described species from lowland indigenous forest sites in New Zealand. (3rd April 2019) - Beveridge, Peter; Glenny, David; Shepherd, Lara
ABSTRACT: Introduction. Cheilolejeunea morganii Bever. & Glenny, a new species of Cheilolejeunea from a lowland forest habitat in eastern Taranaki in the North Island of New Zealand, is described and illustrated. Methods. DNA sequences were extracted from recently collected material at two locations and compared with those for species in a published phylogeny of the genus to establish the position of C. morganii . Photographic images were obtained of key features of the species for the preparation of illustrations for publication. Key results. Cheilolejeunea morganii does not match any species described for New Zealand or Australia. The sequencing results indicate its position in the phylogeny is close to Section Paroicae. A key to the New Zealand species of Cheilolejeunea is provided. Conclusions. In the Australasian flora, C. morganii is distinguished from other species by its combination of monoicy, pycnolejeuneoid gynoecial innovations, lobule length less than 50% lobe length and a multicellular second lobule tooth with 3–4 cells uniseriate. A case is presented for the recognition of the species as a New Zealand endemic.